2021
DOI: 10.1186/s12891-020-03933-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three treatment methods for simple bone cyst in children

Abstract: Background The unicameral bone cyst (UBC) is a kind of benign tumor whose clinical treatments and efficacy are controversial. The purpose of this study was to evaluate the efficacy of the elastic stable intramedullary nail (ESIN), the injection of autologous bone marrow (ABM), and the combination of ESIN and ABM in the treatment of bone cyst in children. Methods Eighty-three cases with simple bone cyst were analyzed retrospectively. Twenty-eight ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Such lesions will gradually separate with age, and the cyst may eventually heal itself and be replaced by normal bone tissue ( 10 ). Assessing the risk of pathological fracture is the most important part of clinical treatment and an important determining factor of surgical intervention ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions will gradually separate with age, and the cyst may eventually heal itself and be replaced by normal bone tissue ( 10 ). Assessing the risk of pathological fracture is the most important part of clinical treatment and an important determining factor of surgical intervention ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment outcomes of 1,829 patients managed with injection were described in 43 studies 1,3-6,10,16,21,25,27,29,30,38,43,46,50,54,56,60,61,69,70,73-75,78,81,83,87,88,91,92,94,95,98-104,106,108 . Among these, 39 studies with a total 1,631 patients with UBCs described whether decompression of the cyst wall was performed in addition to treatment with injection 1,3-6,10,16,21,27,29,30,32,43,45,46,50,54,56,60,61,69,70,73,74,78,81,83,87,88,91,92,94,95,97,99,101-103,106,108 . Outcomes of patients treated with curettage were described in 61 studies 1,3,4,7,8,17-20,23,24,26,28,31,34,35,37,39,41-44,47,48,…”
Section: Methodsmentioning
confidence: 99%
“…A total of 4,973 patients with UBCs from 109 studies were included in our systematic review 1,3-10,15-40,41-70,71-110,111-115 . The number of cysts taken from each study ranged from 10 19,38,57,100,105 to 319 104 (Supplementary Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Various treatment options for solitary bone cysts have been reported to date, including allograft or autograft bone grafting following curettage, injection of autogenous bone marrow or steroids, and insertion of an elastic stable intramedullary nail. In a retrospective study, Zhang et al reported that the complete cure rate according to the Capanna criteria of autogenous bone marrow injection combined with an elastic stable intramedullary nail, elastic stable intramedullary nail alone, and autogenous bone marrow injection alone were 96 %, 82 %, and 46 %, respectively [ 24 ]. Zhang et al reported that the complete cure rate of steroid injection combined with an elastic stable intramedullary nail was 78 % [ 25 ].…”
Section: Main Textmentioning
confidence: 99%